Outline, Divergence Times, and Phylogenetic Analyses of Trechisporales (Agaricomycetes, Basidiomycota) - Liu, Zhan-Bo; Wu, Ying-Da; Zhao, Heng; Lian, Ya-Ping; Wang, Ya-Rong; Wang, Chao-Ge; Mao, Wei-Lin; Yuan, Yuan (Frontiers in Microbiology, 2022)
A new family of Trechisporales, Sistotremastraceae fam. nov. is proposed based on the combination of molecular and morphological data, and it is typified by Sistotremastrum. The phylogenetic analyses inferred from the nuc rDNA ITS1-5.8S-ITS2 (ITS) dataset and the combined 2-locus dataset [5.8S + nuc 28S rDNA (nLSU)] of taxa of Trechisporales around the world, show that Sistotremastraceae forms a monophyletic lineage with robust support within Trechisporales. The Bayesian evolutionary and divergence time analyses on two datasets of 5.8S and nLSU sequences indicate an ancient divergence of the new family from Hydnodontaceae during the Triassic (224.25 Mya). The new family is characterized by resupinate and thin basidiomata, smooth, verruculose or odontioid-semiporoid hymenophore, a monomitic hyphal structure, and generative hyphae bearing clamp connections, the presence of cystidia and hyphidia in some species, thin-walled, smooth, inamyloid and acyanophilous basidiospores. In addition, four new species are described and illustrated, i.e., Trechispora dentata, T. dimitiella, T. fragilis and T. laevispora. Besides, three new combinations, i.e., Brevicellicium daweishanensis, B. xanthum and Sertulicium limonadense, are also proposed based on examination of type materials and phylogenetic analyses of type sequences.